Low latitude geomagnetic signatures following two major solar energetic particle events at different phases of solar cycle-23 - Rawat, Rahul; Alex, S.; Lakhina, G.S. (My University, 2006)
Occurrence of transient astrophysical phenomena is well known to enhance greatly during the solar maximum period. Acceleration of energetic particles takes place in abundance at heliosphere by different transient processes, giving rise to solar energetic particle (SEP) events. Solar cycle 23 witnessed many powerful solar flares and coronal mass ejections producing intense solar energetic particle events, out of which two intense SEP events will be dealt with in the present work. One of the events occurred at solar maximum period and the other during the descending phase. The present work discusses role of interplanetary and solar wind conditions in generation and subsequent development of geomagnetic storms for the events under study. The SEPs are found to exhibit varying intensities, counts and ionic charges in different elements. A comparison of elemental and isotopic abundance variation, the subsequent formulation, development and decay of storm main phase is discussed in current work.
Keywords: Coronal mass ejections; Geomagnetic storms; Solar energetic particle; Solar cycle